Acyclovir Lauriad®: a muco-adhesive buccal tablet for the treatment of recurrent herpes labialis. Issue 3 (March 2014) - Downing, Christopher; Moayyad, Jonathan; Tamirisa, Aparna; Tyring, Stephen
<x xml:space="preserve">Abstract</x> The treatment of recurrent herpes labialis remains a challenge in the 21st century. The virus is ubiquitous and there is no vaccine against the disease. Although recurrence episodes are usually of shorter duration than the primary episode, they are debilitating to patients and there is significant stigma associated with the disease. Acyclovir Lauriad® is a new topical agent that was approved by the US FDA in 2013 for the treatment of recurrent herpes labialis, which affects approximately 20–40% of the population worldwide. The drug is a muco-adhesive tablet, applied to the upper gum at the onset of prodromal symptoms. Utilizing Lauriad® technology, a biologically active compound traverses the mucous membrane to deliver a high concentration of acyclovir directly to the site of the herpes simplex virus infection. Data from a Phase III clinical trial shows that this may be a promising therapy for patients with recurrent herpes labialis.